2013
DOI: 10.1021/es401115q
|View full text |Cite
|
Sign up to set email alerts
|

The Good, the Bad, and the Toxic: Approaching Hormesis in Daphnia magna Exposed to an Energetic Compound

Abstract: A hormetic response is characterized by an opposite effect in small and large doses of chemical exposure, often resulting in seemingly beneficial effects at low doses. Here, we examined the potential mechanisms underlying the hormetic response of Daphnia magna to the energetic trinitrotoluene (TNT). Daphnia magna were exposed to TNT for 21 days and a significant increase in adult length and number of neonates was identified at low concentrations (0.002 – 0.22 mg/L TNT) while toxic effects were identified at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…Hormesis is a dose-response phenomenon and describes a stimulating effect of sub-inhibitory concentrations of toxic substances in organisms [23]. A hormetic response is characterized by an opposite effect at high and low doses of chemical exposure, often resulting in beneficial effects at low quantities [23].…”
Section: Toxicity Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hormesis is a dose-response phenomenon and describes a stimulating effect of sub-inhibitory concentrations of toxic substances in organisms [23]. A hormetic response is characterized by an opposite effect at high and low doses of chemical exposure, often resulting in beneficial effects at low quantities [23].…”
Section: Toxicity Evaluationmentioning
confidence: 99%
“…Hormesis is a dose-response phenomenon and describes a stimulating effect of sub-inhibitory concentrations of toxic substances in organisms [23]. A hormetic response is characterized by an opposite effect at high and low doses of chemical exposure, often resulting in beneficial effects at low quantities [23]. Hormetic growth stimulation has frequently been observed in different biological systems (animals, plants, and microorganisms) exposed to low concentrations of a great variety of chemical compounds such as heavy metals, pesticides, organic arsenic compounds and antibiotics [24].…”
Section: Toxicity Evaluationmentioning
confidence: 99%
“…Calabrese (2010) asserted that hormesis is a generalized phenomenon rather than an exceptional case. Numerous studies have revealed that many chemicals such as bisphenol A, energetic trinitrotoluene, pesticide and antibiotic to cell, bacteria or plant display the non-monotonic concentration response (Bouskine et al, 2009;Belz et al, 2011;Pupo et al, 2012;Gressel and Dodds, 2013;Sheng et al, 2013;Stanley et al, 2013;Vandenberg et al, 2013). In our previous work, we also found the HCRs of some organic solvents, ionic liquids and inorganic salts to Vibrio qinghaiensis sp.-Q67 and firefly luciferase Zhang et al, 2013a,b).…”
Section: Introductionmentioning
confidence: 50%
“…This organism currently lacks genomic/genetic and molecular tools necessary for advanced research. A recent study by (Stanley et al, 2013) used an integrative approach that included transcriptomics, lipidomics, and apical endpoints to link effects on lipid metabolism to hormetic effects (increased growth and reproduction) on D. magna. Similar findings and effects have been seen in other species including fathead Table 1 Invertebrate species used as alternative for models or disorders in vertebrates.…”
Section: Use Of Invertebrates As Alternative Model Speciesmentioning
confidence: 99%